DHA-enriched fish oil upregulates cyclin-dependent kinase inhibitor 2A (P16INK) expression and downregulates telomerase activity without modulating effects of PPARγ Pro12Ala polymorphism in type 2 diabetic patients: A randomized, double-blind, placebo-controlled clinical trial. Issue 1 (February 2018) - Toupchian, Omid; Sotoudeh, Gity; Mansoori, Anahita; Abdollahi, Shima; Ali Keshavarz, Seyyed; Djalali, Mahmoud; Nasli-Esfahani, Ensieh; Alvandi, Ehsan; Chahardoli, Reza; Koohdani, Fariba
Summary: Objective: The present study investigated the effects of docosahexaenoic acid (DHA)-enriched fish oil supplement on telomerase activity, mRNA expression of P16 INK, IL-6, and TNF-α considering Pro12Ala polymorphism in the PPARγ gene. Methods/Design: In this double-blind randomized controlled trial, 72 PPARγ Pro12Ala polymorphism genotyped type 2 diabetic patients aged 30–70 years were randomly assigned to receive 2.4 gr of DHA-enriched fish oil or a placebo for 8 weeks. Genotyping of the Pro12Ala polymorphism in the PPARγ gene was assessed using polymerase chain reaction-restriction length polymorphism (PCR-RFLP), telomerase activity in the peripheral blood mononuclear cell (PBMC) was measured using PCR-ELISA based on the telomeric repeat amplification protocol (TRAP), and changes in the mRNA expression of P16, IL-6, and TNF-α were measured using real-time quantitative reverse transcription–polymerase chain reaction (RT-PCR). Results: In the DHA group, telomerase activity was decreased (p = 0.001) during the intervention. In addition, between-group comparisons showed significant differences in the changes in telomerase activity (p = 0.003) and P16 mRNA expression (p = 0.028) and non-significant differences in TNF-α and IL-6 mRNA expression. The gene*DHA interaction could not affect changes in P16, IL-6, or TNF-α mRNA expression or in telomerase activity in PBMC. Discussion: Short-time DHA-enriched fish oil supplementation caused increased levels of P16 expression and a decline in telomerase activity compared with the control group without modulating the effects of Pro12Ala polymorphism on the PPARγ gene. Because of the positive correlation between P16 activity and cellular senescence, the possibility of senescence stimulation by DHA is proposed.